Implementing of forking after withholding FAW attack on bitcoin system - Alahmadi, Ahmed Mohammed A. (2018)
Nowadays many applications have employed the blockchain technology from sam- ple cryptocurrency to smart contracts applications. Bitcoin is one of the cryp- tocurrency application and digital payment system. It is considered as the first decentralized digital currency system. It was invented by unidentified person or group under the name of Satoshi Nakamoto in 2009 (Nakamoto, 2008). The most three features should be achieved by Bitcoin are decentralized, users anonymity, and consensus. In order to achieve these vital features the Bitcoin system should be provably secure against the attacks. Many attacks have been proposed to change unfairly the reward system of the mining pool and allow the malicious miners to earn undue wage. Selfish Attack, Block Withholding (BWH) Attack and Fork- ing After Withholding (FAW) Attack are three attacks which abusing the reward system and letting the infiltration miners to receive un unearned profits and as a sequence this will affect the decentralized feature of the Bitcoin system. Some studies proposed a solution for Selfish Attack and Block Withholding attack such (Eyal and Sirer, 2014b) and (Bag et al., 2017). FAW attack is first introduced by (Kwon et al., 2017) where this attack combines two attacks: Selfish and BWH attacks. In order to come up with a solution for FAW attack (Kwon et al., 2017) propose partial countermeasures for preventing their FAW attack. However, their solution is neither perfect nor practical. Therefore this study addresses this attack and analyzes its strategy then come up with a prevention solution. The result of this study shows that our prevention solution is practical and more effcient.